Acupuncture for the Treatment of Depression and Physical Symptoms in Chronic Bipolar Disorder: A Case Report. Issue 13 (October 2020) - Matsuura, Yuto; Watanabe, Yoshinori; Taniguchi, Hiroshi; Koga, Yoshihisa; Yasuno, Fumiko; Sakai, Tomomi
Introduction: Bipolar disorder (BD) is typically treated by pharmacotherapy. However, pharmacotherapy alone is often not adequate to cope with the variety of symptoms associated with BD. The present case report describes the therapeutic effects of manual acupuncture on a patient with chronic BD, and multiple concurrent physical symptoms, that did not improve with standard pharmacotherapy. Case: A 41-year-old woman with type II BD presented with depression, anxiety, and multiple physical symptoms. Her symptoms had first appeared 12 years prior, and she was diagnosed with type II BD 3 years after symptom onset. Although she received standard treatment, including medication and psychotherapy, her symptoms did not improve. Acupuncture treatment aimed at improving psychiatric and physical symptoms was performed weekly for 12 weeks. Depression and anxiety symptoms were evaluated using the Himorogi Self-Rating Depression Scale (HSDS) and Himorogi Self-Rating Anxiety Scale (HSAS) respectively. A visual analog scale (VAS) was used to evaluate physical symptoms including diarrhea, insomnia, and general malaise. Outcome measures were evaluated before each treatment. Results: Throughout the course of the acupuncture intervention, no changes were made to the patient's psychotropic medication regimen. HSDS and HSAS scores decreased after 12 weeks of acupuncture treatment and improvements in all physical symptoms, as measured by the VAS, were observed. Furthermore, psychiatric symptoms with hypomanic or mixed features were not exacerbated. Conclusions: In this patient, acupuncture was effective in improving psychiatric and physical symptoms of type II BD. This non-pharmacological intervention may be a viable option for the treatment of BD-associated symptoms.